2013
DOI: 10.1080/17429145.2013.846420
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cyanogenesis and latex stability on tapping panel dryness in rubber trunk girth

Abstract: The presence of high cyanogenic glycoside concentrations may predispose plant to the tapping panel dryness (TPD). This study aimed to verify the involvement of cyanogenesis in the reduction of latex stability and in the establishment of TPD. The following parameters were evaluated in rubber tree trunk bark: concentration of cyanogenic glycosides with determination of cyanogenic potential (HCNp) and latex stability with lutoid bursting index (LBI). The study of the relationship between cyanogenesis and TPD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In aggravated conditions, an irreversible-type of TPD occurs that is called brown bast TPD (BB-TPD) ( Figure 1 g–i). The latter involves histological deformation of bark due to thylosoid formation, lignified gum, and abnormal division of parenchyma cells, and may be related to a cyanogenesis process [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In aggravated conditions, an irreversible-type of TPD occurs that is called brown bast TPD (BB-TPD) ( Figure 1 g–i). The latter involves histological deformation of bark due to thylosoid formation, lignified gum, and abnormal division of parenchyma cells, and may be related to a cyanogenesis process [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tapping cut of some treated trees started to secrete latex, but the latex was immediately coagulated (high plugging index), leading to low yield due to the short duration of flow during tapping. This effect was probably due to higher cyanogenesis on the laticifers that resulted in unstable latex [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the advanced stage, an irreversible type of total dryness, called bark necrosis [9] or brown bast TPD (BB-TPD), can occur [3]. The latter, which is related to a cyanogenesis process [7,10], involves histological deformation of the bark including browning, thickening, or even flaking due to thylosoid formation, lignified gum, and abnormal division of parenchyma cells [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the literature on physiological mechanism of latex agglutination is relevant and led to some functional models ( Berthelot et al., 2014 , 2016 ; Wititsuwannakul et al., 2008a , 2008b , 2008c ). Besides the role of redox metabolism, relationship between cyanogenesis and latex stability was determined at the onset of irreversible TPD ( de Faÿ et al., 2010 ; Moraes et al., 2014 ). Some authors observed an increase in TPD when latex thiol, inorganic phosphorus and pH value decreased ( Guo et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%